AN ANALYSIS OF TEACHERS' LESSON PLANS BASED ON 2013 CURRICULUM - Puspita, Annisa Dwi (2015)
The aims of this study were to investigate whether the teachers' lesson plans are relevant to the 2013 Curriculum or not and to examine the problems faced by the teachers in developing the lesson plans based on the 2013 Curriculum. An English teacher was volunteering as the participant in this study. This study used qualitative method. The data were collected from document analysis and interview. All the data obtained were analyzed qualitatively. The findings showed that the teacher applied and reflected the format and elements of lesson plan based on the Decree of Minister of National Education No.65/2013. It was started from stating indicators and learning objectives, designing learning material and activities for the students also assessing the students. However, in developing learning activities, the teacher did not implement the stages of scientific approach as stipulated by the Ministerial Regulation No. 65/2013. As the interview data indicated, the teacher faced some problems in developing lesson plans based on 2013 Curriculum, including the difficulties to state the indicators and learning objectives, to select appropriate materials or contents, and to develop activities and assessment.